2011
DOI: 10.1007/s10337-011-2156-6
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Illicit Drugs in Urine and Plasma by Micro-SPE Followed by HPLC–MS/MS

Abstract: Confirmation of identity of forensically relevant compounds, such as drugs of abuse, is a necessary step in medico-legal event controls of people involved in crimes, workplace accidents and driving under the influence of drugs (DUID). Plasma is a useful medium in determining the short-term use of illicit drugs and its analysis is mandatory in the case of DUID in many countries. Urine has been the sample of choice for monitoring drug abuses in workplaces and is subjective to strict regulations. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Precision was determined at three different drug concentration levels in plasma (0.1, 0.5 and 5 μg ml -1 ), and the coefficients of variation were acceptable (Table 2). Napoletano et al (2012) obtained similar results, and other authors (Bassan et al, 2011;Dowling & Regan, 2011;Ramírez Fernández et al, 2013) also using LC-MS/MS for determinations reported higher precision values.…”
Section: Validation Of the Proposed Analytical Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…Precision was determined at three different drug concentration levels in plasma (0.1, 0.5 and 5 μg ml -1 ), and the coefficients of variation were acceptable (Table 2). Napoletano et al (2012) obtained similar results, and other authors (Bassan et al, 2011;Dowling & Regan, 2011;Ramírez Fernández et al, 2013) also using LC-MS/MS for determinations reported higher precision values.…”
Section: Validation Of the Proposed Analytical Methodssupporting
confidence: 80%
“…Napoletano et al . () obtained similar results, and other authors (Bassan et al ., ; Dowling & Regan, ; Ramírez Fernández et al , ) also using LC‐MS/MS for determinations reported higher precision values.…”
Section: Resultsmentioning
confidence: 96%
“…MEPS and μ-SPE have been less used, however both the techniques were shown to be suitable for multiclass analytes determination in plasma, saliva and urine by LC-MS/MS [12,13], with a few simple steps obtaining optimal recoveries and great matrix effect reduction. DPX was also described in the 96-well plates format for high-throughput cleanup [14].…”
Section: Where Do We Stand With Microsampling In Illicit Drug Testing?mentioning
confidence: 98%
“…In addition to the serious risks to individuals using these substances, they may also present a threat to non‐users who are potentially in contact with users, for example, during driving or in the workplace. Evidence suggests that driving under the influence of drugs (DUID) is a risk factor and the cause of the recent increase in road accidents …”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that driving under the influence of drugs (DUID) is a risk factor and the cause of the recent increase in road accidents. [5][6][7] Generally, screening tests are rapid, sensitive, and inexpensive; however, they lack high selectivity and may be subject to a false positive result due to cross-reactivity with other non-targeted drugs of similar chemical structure. 8 Any specimen, which has been presumptively screened positive, should be subject to confirmatory testing to eliminate false-positive results.…”
Section: Introductionmentioning
confidence: 99%